Do clutch players win the game? Testing the validity of the clutch player's reputation in basketball - Solomonov, Y.; Avugos, S.; Bar-Eli, M. (Psychology of Sport and Exercise, 2015)
Objectives: The sport psychology literature recognizes the existence of clutch behavior among elite athletes. The present study questions the validity of the clutch reputation in basketball. The performance of clutch players was compared to that of their teammates, using a broad approach that included different performance measures. Design: Eight basketball experts ranked NBA players according to their perceived reputation of being clutch shooters. The selection procedure resulted in a sample of 16 clutch players who had successfully made a game-deciding shot, or had made a successful shot in the final few minutes to tie the game, during the 2003-2006 seasons. Method: Data were collected from play-by-play reports of 222 tied NBA games during the 2005-2006 season and playoffs. Data were reduced to the final five minutes of the second and fourth quarters in each close/tied game. A MANOVA and several ANOVAs were conducted in order to compare the performance measures of the clutch players and the average of their teammates, in game phases of low and high pressure. Results: The reported main effects of clutch versus non-clutch players suggest a superior performance of the clutch players. The results also show that the clutch players improved their performance in the final, most decisive phase of the game, which could be interpreted as evidence for clutch ability. However, the clutch players did not improve their general shooting skills, as might have been expected. Conclusions: Top NBA players, like most other people, do not perform better under pressure situations, at least not while considering their chances of making a shot, but clutch players do influence the end-result of the game in other aspects.